Формирование антиалкогольной компетентности студенток в разных формах физического воспитания - Бакико, И. В.; Савчук, С. А.
The article covers methods of forming anti-alcohol competence of students in physical education universities. It is noted that the author’s technique is eff ective because the level of knowledge among girls is much improved.
Keywords: Физическая культура